2017
DOI: 10.11646/zootaxa.4294.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Archaeochionelasmus nekvasilovae gen. et sp. nov. (Cirripedia, Balanomorpha, Chionelasmatoidea) from the Bohemian Cretaceous Basin (Czech Republic): the first bona fide Cretaceous neobalanoform

Abstract: This paper records a new sessile cirripede from a nearshore, shallow-water facies at Předboj near Prague, Czech Republic. The new taxon, Archaeochionelasmus nekvasilovae gen. et sp. nov., is the earliest known neobalanoform barnacle, and while it may have been an obligate commensal of a cephalopod or marine reptile, that it was a shore barnacle cannot be ruled out. (Zoobank registration: urn:lsid:zoobank.org:pub:177CC951-CEC1-425C-B693-46ADB83BD5D9)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 447 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…They are common at middle and high latitudes (Raymond & Stetson 1932;Hoskin & Nelson 1969;Milliman 1972;Müller & Milliman 1973;Farrow et al 1978;Hottinger 1983;Domack 1988;Nelson et al 1988;Scoffin 1988;Wilson 1988;Taviani et al 1993;Henrich et al 1995;Frank et al 2014;Buckeridge 2015), but they can also thrive at low-latitudes, especially in nutrient-rich environments (Glynn & Wellington 1983;Carannante et al 1988;Halfar et al 2006;Westphal et al 2010;Michel et al 2011;Reijmer et al 2012;Klicpera et al 2013;Reymond et al 2016). The fossil record of encrusting cirripedes starts in the Cretaceous (if primitive forms like Archaeochionelasmus Kočí, Newman & Buckeridge, 2017 in Kočí et al 2017 are included), but it is only during the Neogene that barnacles became really frequent in the shallowwater environments that they presently master (Darwin 1854;Newman et al 1969;Foster & Buckeridge 1987;Doyle et al 1997;Buckeridge 2015).…”
Section: Introductionmentioning
confidence: 99%
“…They are common at middle and high latitudes (Raymond & Stetson 1932;Hoskin & Nelson 1969;Milliman 1972;Müller & Milliman 1973;Farrow et al 1978;Hottinger 1983;Domack 1988;Nelson et al 1988;Scoffin 1988;Wilson 1988;Taviani et al 1993;Henrich et al 1995;Frank et al 2014;Buckeridge 2015), but they can also thrive at low-latitudes, especially in nutrient-rich environments (Glynn & Wellington 1983;Carannante et al 1988;Halfar et al 2006;Westphal et al 2010;Michel et al 2011;Reijmer et al 2012;Klicpera et al 2013;Reymond et al 2016). The fossil record of encrusting cirripedes starts in the Cretaceous (if primitive forms like Archaeochionelasmus Kočí, Newman & Buckeridge, 2017 in Kočí et al 2017 are included), but it is only during the Neogene that barnacles became really frequent in the shallowwater environments that they presently master (Darwin 1854;Newman et al 1969;Foster & Buckeridge 1987;Doyle et al 1997;Buckeridge 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Dr Kočí kindly provided excellent images of the fossil in 2014 and one of us (ASG) expressed his doubts to him then, and to Dr Newman, as to its affinities, suggesting that it was a molluscan fragment. However, the authors believed it to be a cirripede, with eventual publication (Kočí et al, 2017). An anonymous referee for this publication also suggested that the specimen was part of a rudist.…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…This find would put the first appearance of the group back by nearly 40 million years, to a time before the first occurrence of putative ancestors of the neobalanomorphs (Gale and Sørensen, 2014). The specimen was used by Kočí et al (2017) as the basis for a reappraisal of the homologies, phylogeny and origin of the balanomorphs. Dr Kočí kindly provided excellent images of the fossil in 2014 and one of us (ASG) expressed his doubts to him then, and to Dr Newman, as to its affinities, suggesting that it was a molluscan fragment.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations